2021
DOI: 10.1002/ejic.202100304
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling All‐Inorganic CsPbI3 and CsPbI2Br Perovskite Thin Films Formation – Black Phase Stabilization by Cs2PbCl2I2 Addition and Flash‐Annealing

Abstract: Phase formation and transformation of 3D inorganic halide perovskites CsPbI3 and CsPbI2Br were investigated by in‐situ X‐ray diffraction (XRD) in nitrogen or air from 30 °C up to 320 °C. Thin films were obtained by spin‐coating of a liquid solution of salt precursors dissolved in DMSO under normal conditions. XRD data analysis, by using the Le Bail method, evidenced for the first time, to our knowledge, the spontaneous crystallization of black orthorhombic γ phase at ambient temperature, for both 3D perovskite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Rietveld refinement, which could provide a more accurate analysis, cannot be reliably applied to thin films like the ones herein studied. [25] The source of this strain comes from the growth of crystallites within the voids of the scaffold and might prevent or hinder the formation of the unwanted yellow phase while helping the stabilization of the alpha phase at only 100 °C, as it has been proposed before. [26,27] Strain applied during crystal growth may alter the phase diagram of a determined system, and eventually modify the temperatures at which transitions occur.…”
Section: Microstructure and Crystalline Phasementioning
confidence: 97%
“…Rietveld refinement, which could provide a more accurate analysis, cannot be reliably applied to thin films like the ones herein studied. [25] The source of this strain comes from the growth of crystallites within the voids of the scaffold and might prevent or hinder the formation of the unwanted yellow phase while helping the stabilization of the alpha phase at only 100 °C, as it has been proposed before. [26,27] Strain applied during crystal growth may alter the phase diagram of a determined system, and eventually modify the temperatures at which transitions occur.…”
Section: Microstructure and Crystalline Phasementioning
confidence: 97%
“…In our previous work, we have shown that the perovskite crystallization process was slowed down in the presence of the 2D phase [10] . This crystallization process seems even further slowed down in the presence of indium.…”
Section: Resultsmentioning
confidence: 86%
“…[13,31] In our previous work, we have shown that the perovskite crystallization process was slowed down in the presence of the 2D phase. [10] This crystallization process seems even further slowed down in the presence of indium. On the SEM images of Figure 4, it seems that the grains discernible at this resolution for the 3D phase are reduced in size for the [3D + 2D] mixture.…”
Section: Influence Of the Indium Addition In [3d + 2d] Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CsPbI 3 delta phase was expected as the films were taken out to ambient atmosphere for the measurement and this material rapidly transitions to this phase when in contact with moisture. [ 17,18 ]…”
Section: Resultsmentioning
confidence: 99%